Discovery of A Novel Synthetic Thiazole-benzimidazole Conjugate that Acts as a Potent Pancreatic Lipase Inhibitor using in silico and in vitro Approaches - Abouzied, Amr Salah; Khaled Bin Break, Mohammed; Huwaimel, Bader; Hussein, Weiam; Alafnan, Ahmed; Mahmoud Younes, Kareem (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/ Background: Pancreatic lipase (PL) inhibition has been suggested to be an effective method for obesity management. In this study, 10 novel thiazole-benzimidazole conjugates were designed. Materials and Methods: Conjugates were initially screened via in silico experiments, such as ADMET analysis and molecular docking, to identify the most promising PL inhibitors. Results: Results revealed that compounds 3, 6 and 8 had the most optimum drug likeness properties, and the highest binding affinity to PL, with binding energies of -7.7, -7.5 and -8.1 kcal/mol, respectively. Therefore, these promising derivatives were then synthesized and subjected to an in PL inhibition assay to validate the results of the in silico experiments. The synthetic compounds were fully characterized via FTIR, 1H-NMR, 13C-NMR and LCMS. Results of the enzymatic assay revealed that 3, 6 and 8 inhibited PL potently with high inhibition rates of greater than 80% at the highest tested dose, and demonstrated IC50 values of 68.53, 54.97 and 50.09 μM, respectively. Compound 8 was the most active derivative and displayed comparable activity to orlistat which possessed an IC50 value of 39.18μM. Conclusion: Therefore, we report the discovery of compound 8 as a highly potent PL inhibitor that could act as a lead compound to develop novel anti-obesity agents.
Keywords: Pancreatic lipase; Inhibition; Thiazole-benzimidazole; in silico; in vitro; Enzyme assay